Assessment of Bioactive Resin-Modified Glass Ionomer Restorative as a New CAD/CAM Material. Part I: Marginal Fitness Study - Huda A. Abdulla1, Manhal A. Majeed2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The objective of this in vitro study was to evaluate and compare the marginal fitness of monolithic crowns fabricated from a newly developed bioactive CAD/CAM resin block and reinforced resin CAD/CAM block pre-and post-cementation with adhesive and self-adhesive resin cements. Bioactive CAD/CAM block were fabricated from ACTIVA BioACTIVE-RESTORATIVE (Pulpdent Corporation, USA) using a clear rectangular Teflon mold. Thirty-two human maxillary first premolar teeth were prepared to receive full crowns then divided into two main groups of 16 teeth each according to the type of block used to fabricate the crowns: Group A: crowns fabricated from the bioactive resin block, Group B: crowns fabricated from reinforced composite block (BRILLIANT Crios, Coltene). Each group was then subdivided into two subgroups according to the type of resin cement used for cementation, Subgroups (A1, B1): RelyX Ultimate cement, Subgroups (A2, B2): ACTIVA BioACTIVE-cement. The prepared teeth were scanned using CEREC Omnicam digital intra-oral and the crowns were then designed using CEREC Premium software (version 4.4.4) and milled using CEREC MC XL milling unit. The marginal gap of each crown was measured before cementation at four points on each tooth surface using a digital microscope at a magnification of 230x. Each crown was then cemented on its respective tooth according to the manufacturers’ instructions of each cement, and the marginal gap was measured again at the same aforementioned points. The results of this study showed that the marginal gap of all groups are below the clinically acceptable limit. Meanwhile, the marginal gap of the crowns fabricated from both block types increased significantly after cementation with both types of cement. Pre-cementation, student’s t-test revealed that there is no statistically significant difference in the marginal gap of crowns fabricated from both block types (p> 0.05). Post-cementation, a statistically highly significant difference was seen between both block types with both types of cement (p<0.01). From the results of this study, the newly developed bioactive resin block seems a promising material for CAD/CAM applications in terms of marginal fitness.